Comparison of Different Extraction Methods on Sorghum Seeds (Shorgum bicolor (L). Moench) on Extract Yield and Secondary Metabolite Compound Levels - Maramis, Rilyn Novita; Nahor, Evelina Maria; Rindengan, Elvie Rifke (Jurnal FARMASIMED (JFM), 2025)
Sorghum, as a potential crop, has been promoted by the government as a national food source. Sorghum contains primary metabolites such as carbohydrates, proteins, and high fiber, as well as secondary metabolites including alkaloids, tannins and phenols, steroids, and terpenoids. The secondary metabolites produced and the yield obtained depend on the extraction method used. This study aimed to determine the yield and concentration of sorghum seed extract obtained through cold extraction (Percolation) and hot extraction (Reflux). Sorghum seed extract was obtained using cold (Percolation) and hot (Reflux) extraction methods with 96% ethanol as the solvent. The resulting yield was then calculated, followed by identification and quantification using UV-Vis spectrophotometry. The results show that the cold extraction (Percolation) method produced a yield of 3,733%, while the hot extraction (Reflux) method produced a yield of 10,133%. The identification of secondary metabolites in sorghum seed extracts from both cold (Percolation) and hot (Reflux) extraction methods reveals the presence of saponins, flavonoids, tannins, and terpenoids, but no alkaloids or steroids. The percolation method yields a total saponin content from Quillaja bark of 0,94% w/w, a total flavonoid content equivalent to quercetin of 0,84% w/w, and a total tannin content equivalent to tannic acid of 0,45% w/w. Meanwhile, the reflux extraction method yields a total saponin content from Quillaja bark of 1,07% w/w, a total flavonoid content equivalent to quercetin of 0,0615 %b/b, and a total tannin content equivalent to tannic acid of 19,44% w/w.